Project Risk Management on Agile Development Team: Case Study of an Outsourcing Company in Indonesia - Rima Tamara Aldisa; Pandu Maulana (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
Agile have been widely used by companies. With using of Agile, the project will be more flexible when compared to the traditional method (Waterfall). However, the use of Agile has many challenges, including its agile nature and iterations. This makes us interested in conducting further investigations regarding risk management practices in Agile following an outsourcing company in Indonesia. The system created is in the form of a job marketplace in which there are job vacancies to support outsourced activities at the company. The purpose of this research is to identify what risks are faced related to development with Agile methods at the company. Related to this, identification will be carried out using risk management combined with Agile development methods. The results of this research indicate that there are four risks that are quite critical in the application of Agile methods, namely human factors, communication factors, changing requirements factors, and schedule factors.